FLORA IERBOASĂ DIN PARCHETELE DE LA CERNOLEUCA (DONDUŞENI) - Mârza, Mihail; Donea, Victor; Nicorici, Ludmila; Mîrza, Eliza; Sîrbu, Tatiana (CEP USM, 2007)
The forests of Moldova have a reduced bioproductive and ecoproductive efficiency, however, the exploitation of the national forest fund is realized by razing cuttings. The result of such kind of exploitation leads to temporary appearance of some communities of sinantropicplants,where the herbal plants prevail. It was found that in the assortment of the herbal plants encountered in cutting (≈over 130 species) in the 1st year over 50% are herbal plants; beginning with the 3rd year, gradually increases the number of the multianual species.
Keywords: plante ierboase